ANALISIS PEMBELAJARAN MANDIRI BERBASIS DARING PADA MASA PANDEMI COVID-19 - Meyta Pritandhari; Fajri Arif Wibawa (Lembaga Penelitian UM Metro, 2021)
The Covid-19 pandemic has forced the learning system to change drastically from offline meetings (face to face) to online learning. In this online learning, students are required to be able to do learning independently. Independent learning is learning that is carried out on its own initiative in accordance with the way or learning style that can support the understanding of independent learning. The purpose of this study was to analyze independent learning conducted online. This is done because there are various problems in online independent learning. Students who are accustomed to doing offline learning (face to face) will find it difficult to understand online learning materials. The long-term goal of this research is to evaluate independent learning conducted online.This study uses a qualitative descriptive method using data collection techniques, namely interviews and documentation. Data analysis in this study used interactive model analysis. Online-based independent learning during the COVID-19 pandemic has been carried out well. Independent learning has several positive benefits that can shape the character of students in the learning process. independent learning carried out by students using various applications to support learning activities